Interventions to reduce caesarean section rates at government medical college and hospital Aurangabad, India - Gadappa, Shrinivas; Gemavat, Honey; Deshpande, Sonali; Shah, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean sections are effective in saving maternal and infant lives, but only when they are performed for medically indicated reasons, The Objective of this study was to reduce caesarean Section rate at GMCH, Aurangabad and to improve overall birthing experience with respectful maternity care. Methods: The caesarean sections done at GMCH Aurangabad were audited using Robson`s Ten Group classification system to identify the major contributors to the overall CS rate. The following clinical and non-clinical interventions were applied dynamically to control the caesarean section rates. Clinical Interventions were changes in protocols regarding induction of labour, Intermittent auscultation as opposed to continuous electronic foetal monitoring in low risk cases, use of a partogram, encouragement of different birthing positions, promoting TOLAC to reduce the secondary CS rate. Nonclinical interventions include encouragement of DOULA (birth companion), ante-natal counselling of the expectant mothers, training of healthcare staff for respectful maternity care and use of evidence based clinical practice guidelines with mandatory second opinion for every non recurrent indication of CS. Auditing of caesarean section using Robson classification. Results: In this study there has been steady decline in LSCS rates from 33% to 26.9%. On analysis with Robson classification, group 5 (previous LSCS) made largest contribution of 36.9% followed by Group 1, 2, 10 each contributed 18.01%,13.2% and 11.2% respectively. Group 6 to 10 account for 23%. Various birthing positions lowered use of oxytocics from 33 % to 19% as well lowered episiotomy rates with greater success in vaginal delivery. Conclusions: Modification of induction protocols have reduced the primary LSCS rates and successful VBAC using FLAMM score was helpful in reducing the repeat caesarean Sections. Various birthing positions, DOULA gave greater success in vaginal delivery. LSCS rates in mothers with breech, multiple or oblique/transverse lies were largely unmodifiable. Limiting the CS rate in low-risk pregnancies by individualizing every labour and not to set a time limit as long as mother and baby are closely monitored.